Powstanie i pierwsze lata działalności muzeum Wilhelma Piecka w Gubinie = The establishment and early years of Wilhelm Pieck's Museum in Gubin - Skobelski, Robert (1968- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Wilhelm Pieck, a German and international communist movement activist, was the first and only president of the German Democratic Republic. After his death in 1960, the top PZPR (United Polish Workers' Party) officials ordered the establishment of his museum in Gubin, his birthplace and hometown. The responsibility fell on the regional party's authorities that were to be assisted by KC PZPR's (the party's top management) lnstitute of Party's History and officials from the Ministry of Culture and Arts. They agreed on locating the museum in the Piecks' family house, where GDR's president spent his childhood.
Keywords: Gubin (woj. lubuskie); Gubin - kultura; Muzeum Wilhelma Piecka; Pieck, Wilhelm (niemiecki działacz komunistyczny, 1. prezydent NRD; 1876-1960)